Assessing the impact of cover crops on soil health in a long-term no-till rotation: a case study from Northeast Kansas - Grünberg, Jessica (Kansas State University, 2024)
Maintaining soil health is essential for sustaining agricultural productivity and ecosystem resilience. Conservation agriculture, known for minimal soil disturbance and permanent soil cover, offers strategies to address soil degradation associated with conventional management practices like conventional tillage and prolonged fallow periods. Despite its recognized benefits, there are concerns regarding potential drawbacks, such as nutrient stratification and soil acidification over time. Cover crops have emerged as a promising tool for enhancing soil health, however, long-term effects of cover crops on soil proprieties under no-till management and various intensification schemes remain to be fully understood. This study aimed to assess (i) how different preceding cover crop types and varying nitrogen (N) rates applied to corn influence pH, soil organic carbon (SOC), and nutrient concentrations and distribution in the soil profile, and (ii) the effects of different intensification strategies on soil biological indicators and their persistence throughout subsequent years of the rotation. A long-term experiment consisting of a no-till three-year wheat (Triticum aestivum L.), sorghum [Sorghum bicolor (L.) Moench], soybean [Glycine max (L.) Merr] rotation was established in 2007 near Manhattan, Kansas. Sorghum was replaced with corn (Zea mays L.) in 2020. The different fallow managements imposed between wheat and corn included chemical fallow (CF), double-crop soybean (DSB), and four cover crop treatments. To meet the first objective of this study, soil profile samples were collected in 2021 and 2022 after corn harvest to determine how different fallow management preceding corn and different N rates applied to corn affect soil pH, SOC, Total N, and Melich-3 Phosphorus (P) concentration and their distribution in the soil profile. Nutrient concentrations were higher near the soil surface, and pH tended to decrease in the upper soil layers. Differences among the fallow management options were most pronounced at the 0-5 cm depth for all measurements. Soil organic carbon was enhanced by adding cover crops and DSB compared to CF. Similarly, Total N was greater whenever any cover crop treatment or DSB replaced a portion of fallow. Soil pH increased with cover crops and DSB and decreased with higher N rates only at surface layers. Phosphorus concentrations decreased with DSB and remained similar to CF for most cover crops. Overall, cover crops and intensification alternatives like double-cropping showed potential to improve SOC and N levels in the soil surface and enhance its capacity to buffer changes. Further research should address managing the negative impacts of P stratification on soil health and water quality. To meet the second objective, soil samples were collected in May 2022 and April 2023 in all crop phases, to capture the effect of fallow management on biochemical indicators at different time intervals after cover crop termination: immediately after cover crop termination (T0), in corn stubble one year after cover crop termination (T1), and in growing wheat two years after cover crop termination (T2). Samples were collected at the 0-5 cm depth and analyzed for the following biochemical indicators: POXC, soil protein, glucosidase and glucosaminidase activities, and soil respiration. Cover crops positively impacted all soil biochemical indicators immediately after cover crop termination (T0), increasing POXC by 30%, soil protein by 17%, glucosidase activity by 63%, glucosaminidase activity by 82%, and soil respiration by 116% compared to CF. In general, cover crops with larger biomass inputs provided the largest increases in biochemical indicators. Double-crop soybeans exhibited indicator levels similar to or slightly greater than CF, yet lower than most other cover crops. These responses were most evident immediately after cover crop termination and persisted to some extent for one year thereafter. However, the responses diminished over time and were not detectable two years after cover crop termination. This information could assist in determining how frequently cover crops should be integrated into cropping systems and identify the most effective mixtures and species for sustaining soil health benefits over time.
Keywords: Cover crops; Soil health; No-till; Long-term